THE IMPORTANCE OF PREVENTIVE MEASURES IN PREVENTING OFFENSES AMONG YOUTH (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article analyzes the importance and effectiveness of preventive measures implemented to prevent offenses among youth. It describes effective experiences in crime prevention through methods such as conversations, awareness campaigns, psychological assistance, and public oversight carried out by the Deputy Dean.